Analysis and Comparison of Data Compression Algorithms - Nambiar, Shrenik; Srikanth Kamath, H. (International Journal of Engineering and Technology, 2019)
The amount of data being shared over the internet is increasing exponentially. In this digital age, where even devices like refrigerators are connected, data needs to be stored in compressed form. The compressed data should be retrieved without loss of information else the data will be deemed corrupt. As we are approaching 5G communication, the data need to be transferred over the internet at a higher rate. This cannot be achieved by older compression algorithms which has lesser compression ratio and even lesser compression and decompression speed. In this paper, an analysis of modern compression algorithms along with some older compression algorithms have been conducted. Also the implementation and comparison is conducted. The comparison was done with the help of graphs plotted using MATLAB soft- ware. The compression algorithms compared were Deflate, bzip2, Zstandard, Brotli, LZ4 and LZO. The files used for compression were taken from Canterbury and Silesia Corpus.Â Â Â